Efficient, Correct Simulation of Biological Processes in the Stochastic Pi-calculus - Phillips, Andrew; Cardelli, Luca (Computational Methods in Systems Biology, 2007)
This paper presents a simulation algorithm for the stochastic pi-calculus, designed for the efficient simulation of biological systems with large numbers of molecules. The cost of a simulation depends on the number of species, rather than the number of molecules, resulting in a significant gain in efficiency. The algorithm is proved correct with respect to the calculus, and then used as a basis for implementing the latest version of the SPiM stochastic simulator. The algorithm is also suitable for generating graphical animations of simulations, in order to visualise system dynamics.